2009
DOI: 10.1097/bpo.0b013e31819a85de
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Blood Transfusion Requirements in Pediatric Scoliosis Surgery

Abstract: III, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…Sethna et al [27] used a higher dose of TXA at 100 mg/kg load followed by 10 mg/kg/h, while Neilipovitz et al [28] used a lower dose loading at 10 mg/kg followed by 1 mg/kg/h. In a recent study, when two TXA dosing regimens were evaluated, a dose-dependent effect of TXA on the transfusion requirements was recorded [29]. Although only adolescent idiopathic scoliosis patients were examined, the number of patients included in the study was too low, while surgeries were performed by different surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Sethna et al [27] used a higher dose of TXA at 100 mg/kg load followed by 10 mg/kg/h, while Neilipovitz et al [28] used a lower dose loading at 10 mg/kg followed by 1 mg/kg/h. In a recent study, when two TXA dosing regimens were evaluated, a dose-dependent effect of TXA on the transfusion requirements was recorded [29]. Although only adolescent idiopathic scoliosis patients were examined, the number of patients included in the study was too low, while surgeries were performed by different surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Grant et al 21 showed that, during pediatric scoliosis surgery, the use of TXA decreased the number of intraoperative PRBC transfusions by 50%. In children undergoing craniofacial surgery, only two studies 22,23 showed the effectiveness of an antifibrinolytic drug in reducing intraoperative blood loss.…”
Section: -21mentioning
confidence: 99%
“…In some institutions, anesthesia protocols are standard in scoliosis surgery which leads to limitations in the study 23 . As well, in randomized-control trials, patients' demographic data such as age, gender, body mass index, medical history vary between the two groups contributing to alteration in the results, but such differences are minor and of little or no clinical relevance.…”
Section: Discussion:-mentioning
confidence: 99%